2014
DOI: 10.1186/1477-7827-12-60
|View full text |Cite
|
Sign up to set email alerts
|

The hormonal composition of follicular fluid and its implications for ovarian cancer pathogenesis

Abstract: Ovulation has long been associated with an increased risk in ovarian cancer, yet the underlying molecular mechanisms remain obscure. Two aspects of ovulation have been linked to ovarian cancer pathogenesis. The first is the impact of repetitive tissue injury and repair that occurs with each ovulatory event. The second is the release of follicular fluid that accompanies the follicular rupture and its effect on the ovarian and fallopian tube epithelial cells. Hormones are an important component of follicular flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 76 publications
1
52
0
Order By: Relevance
“…6,34,35 In addition, a model to study follicular fluid effects on fimbria was reported by Bahar-Shany et al, 12 proving the molecular basis and the relative site of ovarian cancer pathogenesis. 36,37 These observations suggest that the carcinogenic pathway originated in the secretory epithelial cells of fimbria, but the molecular mechanism involved is still to be found. Recent studies hypothesize a common oncogenic pathway and similar pathogenetic mechanisms, such as iron-induced oxidative stress derived from retrograde menstruation 7 in epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6,34,35 In addition, a model to study follicular fluid effects on fimbria was reported by Bahar-Shany et al, 12 proving the molecular basis and the relative site of ovarian cancer pathogenesis. 36,37 These observations suggest that the carcinogenic pathway originated in the secretory epithelial cells of fimbria, but the molecular mechanism involved is still to be found. Recent studies hypothesize a common oncogenic pathway and similar pathogenetic mechanisms, such as iron-induced oxidative stress derived from retrograde menstruation 7 in epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While the source of this reprogramming is still under investigation, interaction with the hormone- and growth factor-rich ovarian microenvironment is implicated. Recent studies have highlighted the importance of the hormonal environment of the ovary, and follicular fluid in particular, that can induce DNA damage and mutations [4]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been generally accepted that long-term, excessive exposure to circulating estrogen, which is metabolized to form catechol estrogen, contributes and may be causal to ovarian carcinogenesis. Estrogen is thought to exert its effects in ovarian cancer by enhancing the proliferation of ovarian epithelial cells and increasing their susceptibility to genetic errors during DNA replication (Goodman et al, 2001;Emori and Drapkin, 2014). Accordingly, variations in the genes involved in the biosynthesis and metabolism of estrogen may contribute to altered levels of estrogen and thereby contribute to the risk of ovarian cancer (Holt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%